Ecological Status of Angiospermic Macrophytes in Retension Ponds and Drainage Ditches of Jalpaiguri District, West Bengal, India - Mazumder, Mallika; Sarkar, Anup Kumar (Indian Forester, 2020)
Aquatic angiosperms are very remarkable components of aquatic systems which are very important for the conservation of any biodiversity region. Though the macrophytic communities of rivers, lakes and large aquatic bodies of many biodiversity regions were recorded properly but the macrophytes of small retension pond and drainage ditches were neglected as these are underutilized aquatic bodies. The condition is also same for the district Jalpaiguri. The present study is therefore designed to enumerate the aquatic macrophytes of Retension Ponds and Drainage Ditches of Jalpaiguri District, West Bengal, India. The studies were conducted in between January 2017 to May 2019. In this study 201 angiosperms were recorded under 48 families.